2019
DOI: 10.1111/are.14366
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol inhibitsVibrio harveyihemolysin virulence by reducing its haemolytic activity

Abstract: Vibrio harveyi, as one of the main pathogens of vibriosis, has serious multidrug resistance, which has been a focus for domestic and foreign researchers. Vibrio harveyi hemolysin (VHH), an important virulence determinant of V. harveyi, causes cell necrosis and tissue damage by lysing cell membranes, which is essential for V. harveyi invasion of the host. The critical role of VHH in the virulence of V. harveyi renders it an ideal target for designing novel anti-virulence therapeutics. We found that honokiol, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Honokiol is an isomer of magnolol, they are major phenolic substances derived from the root and bark of M. officinalis (Ho et al, 2001). Recently studies have shown that honokiol reduced Vibrio harveyi haemolysin virulence, with the MIC of 16 μg/ ml (Guo et al, 2019b), magnolol inhibited the haemolytic activity of Aeromonas hydrophila, and the MICs ranged from 32 to 64 μg/ml (Dong et al, 2017). Despite different bacteria species, the reported MICs are higher than our results, which may be attributed to the fact that honokiol and magnolol are more effective in inhibition The MRA method is a simple, accurate and reliable bioassay that is widely used in evaluating natural products and synthetic compounds for antimycobacterial activity (O'Neill et al, 2014;Palomino et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol is an isomer of magnolol, they are major phenolic substances derived from the root and bark of M. officinalis (Ho et al, 2001). Recently studies have shown that honokiol reduced Vibrio harveyi haemolysin virulence, with the MIC of 16 μg/ ml (Guo et al, 2019b), magnolol inhibited the haemolytic activity of Aeromonas hydrophila, and the MICs ranged from 32 to 64 μg/ml (Dong et al, 2017). Despite different bacteria species, the reported MICs are higher than our results, which may be attributed to the fact that honokiol and magnolol are more effective in inhibition The MRA method is a simple, accurate and reliable bioassay that is widely used in evaluating natural products and synthetic compounds for antimycobacterial activity (O'Neill et al, 2014;Palomino et al, 2002).…”
Section: Discussionmentioning
confidence: 99%